Factors Causing Drugs Among Adolescents in Bandar Lampung City - Zainudinhasan, Zainudinhasan; Adnan, Alinda Julietha; Amanda, Mutiara; Sadhana, Putu (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
One of the problems that occurs in Indonesia is drug abuse. The meaning of Narkoba is psychotropic narcotics and other addictive substances. Narcotics or drugs are used as medicinal ingredients and research in medical science. As the years go, the drugs are abused by irresponsible people, causing side effects that are quite dangerous for people. The most users of drugs are teenagers where the teenagers who should be the nation’s relay are destroyed because of drugs.